On-farm cocoa yields increase with canopy cover of shade trees in two agro-ecological zones in Ghana. (28th May 2019) - Asare, Richard; Markussen, Bo; Asare, Rebecca Ashley; Anim-Kwapong, Gilbert; Ræbild, Anders
Abstract : Despite Ghana's large contribution to global cocoa production, average yields are low. Policymakers and practitioners are calling for implementation of a climate smart strategy by increasing yields and augmenting shade tree cover in cocoa systems. However, there have been few studies in West Africa on the relationship between shade and cocoa yield under field conditions. The objective of this study was to determine the effect of shade tree cover and other factors on on-farm cocoa yields over a four-year period. The study was conducted on 86 farm plots of 8–28 years' cocoa trees with varied canopy cover (CC) in Ashanti and Western regions of Ghana. A linear mixed model analysis showed that yields increased significantly with increased CC of shade trees, and indicated a doubling of yields when going from zero to approximately 30% crown cover. Fertilizer use gave a yield increase of 7%. Farms located in Western region had higher yields compared to Ashanti, and cocoa systems on short fallows had lower yields than farms cultivated on recent forest clearings and old fallows. Fungicide use, seed sources and land ownership had no significant effects on yield. We conclude that for a sustainable climate-smart cocoa agenda, promotion of shade trees is key.